The Role of Arbitration Institutions In Resolution of Investment Disputes In Indonesia (Case Study on PT Ferrostaal AG Against PT. Nusantara III regarding Violation of Joint Venture Agreement) - Nanda Utama (Master of Law Program, Ekasakti University, 2025)
Arbitration comes from the word